Mechanisms, Pathophysiology and Currently Proposed Treatments of Chronic Obstructive Pulmonary Disease - Sarah de Oliveira Rodrigues; Carolina Medina Coeli da Cunha; Giovanna Martins Valladão Soares; Pedro Leme Silva; Adriana Ribeiro Silva; Cassiano Felippe Gonçalves- (MDPI AG, 2021)
Chronic obstructive pulmonary disease (COPD) is one of the leading global causes of morbidity and mortality. A hallmark of COPD is progressive airflow obstruction primarily caused by cigarette smoke (CS). CS exposure causes an imbalance favoring pro- over antioxidants (oxidative stress), leading to transcription factor activation and increased expression of inflammatory mediators and proteases. Different cell types, including macrophages, epithelial cells, neutrophils, and T lymphocytes, contribute to COPD pathophysiology. Alteration in cell functions results in the generation of an oxidative and inflammatory microenvironment, which contributes to disease progression. Current treatments include inhaled corticosteroids and bronchodilator therapy. However, these therapies do not effectively halt disease progression. Due to the complexity of its pathophysiology, and the risk of exacerbating symptoms with existing therapies, other specific and effective treatment options are required. Therapies directly or indirectly targeting the oxidative imbalance may be promising alternatives. This review briefly discusses COPD pathophysiology, and provides an update on the development and clinical testing of novel COPD treatments.